Comparison of Asthma Control Test (ACT) with (GINA) guidelines in the Assessment of Asthma Control and determine if can use Asthmda Control Test ACT as alternative to Gina guidelines in control asthma. - Sultan, Kassim M.; Al.Obaidy, Muhammed W.; Jaber, Ahmed H. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: The gold standard in assessing asthma control is the Global Initiative for Asthma (GINA) criteria. And because of the difficulties of access to pulmonary functions tests, The ACT has the added  advantage that it does not require lung function assessment.Objectives: The aim of this study is to assess asthma control through ACT score and GINA guideline, and to determine if the ACT can be as useful as the GINA-guidelines criteria in assessing asthma control in Iraq. Patient and method: Cross sectional study with comparing ACT vs. GINA guideline in control of asthma level. This study was conducted at Respiratory consultation unit of the Iraqi National center of early detection   of Cancer, Baghdad-Iraq, The study was conducted during the period from 1stNovember 2012 to 1stJuly 2013. A total of 71 adult asthmatic patients who were attended to the respiratory consultant unit were asked to participate and were enrolled in this study regardless their age or gender. Their asthma diagnosed and proved clinically by a combination of history, clinical finding In addition objective measurements using spirometry(FEV1) measured by the reversibility test which is defined as(an increment of>12% or 200 ml ofFEV1 after 20 minutes of administration of inhaled short acting B2-agonist).Result: There were 71 patients enrolled in this study, of them 66 (92.96%) had an ACT score of ≤ 19 ((26) (39.4%) are male),(40)(60.6%) are female ,and 5 patients (7.04%) had an ACT score of > 19 (only(1) (20.0%) is male and and(4)(80.0%) are female. It had been found the number of male is( 27)and(26)(39.4%) out of them had an ACT19 and number of female is(44),(40)(60.6%)outof them had ACT19. No significant differences had been found in between those patients with ≤19 ACT score vs. those with > 19, regarding the age and gender, in both comparison P>0.05 it had been found that good agreement present between ACT and GINA, 92.9%.ACT agreed the GINA in (37 patients with uncontrolled asthma, 24 patients with partially controlled and 5 patients withcontrolled).Conclusion: ACT can serve as an alternative diagnostic tool in assessing asthma control even without an aid of a spirometer or a peak flow meter. An ACT score of more than 19 can classify patient as controlled asthmatic while an ACT score < 19 can classify the patient as uncontrolled and partially controlled asthmatics.